Preservation of female genetic resources of common carp through oogonial stem cell manipulation - Franěk, Roman; Tichopád, Tomáš; Steinbach, Christoph; Xie, Xuan; Lujić, Jelena; Marinović, Zoran; Horváth, Ákos; Kašpar, Vojtěch; Pšenička, Martin (Cryobiology, 2019)
Several experiments were conducted in order to develop an optimal protocol for slow-rate freezing (-1 °C/min) and short-term storage (-80 or 4 °C) of common carp ovarian tissue fragments with an emphasis on oogonial stem cells (OSCs). Dimethyl sulfoxide (Me2SO) with concentration of 1.5 M was identified as the best cryoprotectant in comparison to propylene glycol and methanol. When comparing supplementation of sugars (glucose, trehalose, sucrose) in different concentrations (0.1, 0.3, 0.5 M), glucose and trehalose in 0.3 M were identified as optimal. Short-term storage options for ovarian tissue pieces at -80 °C and 4 °C were tested as alternatives to cryopreservation and storage in liquid nitrogen. The presence of OSCs was confirmed by immunocytochemistry and viability after storage was determined by the trypan blue exclusion test. This study identified the optimal protocol for OSC cryopreservation using slow rate freezing resulting in ∼65% viability. The frozen/thawed OSCs were labelled by PKH-26 and transplanted into goldfish recipients. The success of the transplantation was confirmed by presence of fluorescent cells in the recipient gonad and later on by RT-PCR with carp dnd1 specific primers. The results of this study can facilitate long-term preservation of common carp germplasm which can be recovered in a surrogate recipient through interspecific germ cell transplantation.
Keywords: kryoprotektivní látky; Propylene Glycol; methanol; Slow-rate freezing; viabilita buněk; Surrogate production; Freezing; trehalosa; Cryopreservation; oogoniální kmenové buňky; Oogonia; Cell Survival; kapři; Oogonial Stem Cells; Trehalose; Methanol; zmrazování; oogonie; Animals; Cryoprotective Agents; propylenglykol; ženské pohlaví; zvířata; Ovary; Carps; dimethylsulfoxid; Gene banking; sacharosa; Dimethyl Sulfoxide; kryoprezervace; Female; Cyprinus carpio; Sucrose; ovarium